The importance of an analytical approach to e-commerce: the case of L’Oréal luxe division - Baptista, Gabriel de Miranda Amaral (2020)
Internship Report presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence